Diagnosis and Management of Acute Otitis Media - Siti Amalya Ilmyasri (Global Health Science Group, 2020)
Acute Otitis Media is a middle ear infection that is often found in children, especially those aged 2 years. This occurs due to the anatomical structure of the ear of a child that is different from that of an adult. The purpose of this study was to determine the correct diagnosis and management of patients with acute otitis media. The method used in this research is literature study from several medical journals, both national and international. Sources used by authors such as NCBI, PubMed, and google schoolar in the 2014-2020 period using the keyword acute otitis media. From about 100 articles obtained, the author used 20 articles to be analyzed in depth using the systematic literature review method. The results obtained in the form of a diagnosis of acute otitis media can be enforced based on history and physical examination. Common symptoms that can be experienced by patients such as fever, ear pain, discharge from the ear, and hearing loss. However, other symptoms can be experienced which vary based on the stage suffered. Treatment of AOM can be done by giving antibiotics which are started when the symptoms and signs of AOM do not improve in two to three days.